In-use product and steel stocks sustaining the urbanization of Xiamen, China - Lulu Song (Taylor & Francis Group, 2019)
Introduction: In-use product and material stocks are the amount of concerned manufactured products and materials in active use, and are essential components of urban ecosystem. Methods: This study estimates the dynamic in-use stocks of steel-containing products and steel in the city of Xiamen, China, during 1980–2015 by applying a bottom-up accounting approach. We incorporate 55 categories of steel-containing products that are classified into five end-use sectors (i.e., buildings, infrastructure, transportation equipment, machinery, and domestic appliances). Outcomes and Discussion: In-use stocks of 51% of the studied products kept increasing during 1980–2015, especially after 2000. Steel stocks have grown up to 4.9 ± 1.4 tons per capita (t/cap) in 2015, from 0.5 ± 0.2 t/cap in 1980. Buildings are the largest reservoirs, although its share decreased from 89% in 1980 to 68% in 2015. The dynamic spatial distribution indicates that steel stocks gradually expanded from urban core to suburban areas. Conclusion: Theresults help to explore how a city’s urbanization is sustained by the in-use stocks growth. In-use steel stocks, of which the growth is highly correlated to and probably driven by the population growth, GDP increase, and urban built-up area expansion, may serve as a supplementary indicator for urbanization.